Surgical tail amputation for severe traumatic coccygeal injury in a sugar glider (Petaurus breviceps) - Raden Roro Allamanda Ardia Wardana; I Putu Krisna Ardhia Pradnyandika; Ni Wayan Apsari Shantika Pratistha (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2026)
Sugar gliders (Petaurus breviceps) are kept as companion animals and may be predisposed to tail injuries due to aggression, self-mutilation, or environmental trauma. This report describes the clinical presentation, surgical management, and postoperative outcomes of tail amputation in a sugar glider with a coccygeal fracture complicated by self-mutilation. A 2-year-old intact male sugar glider presented with reduced appetite, repeated tail biting, and a five-day history of tail injury. Physical examination revealed an open wound with swelling, purulent discharge, pain on palpation, and crepitus. Radiography confirmed a complete transverse fracture of the distal coccygeal vertebra. Tail amputation was performed under anesthesia using 2% lidocaine at 4 mg/kg. The fractured segment was removed, and the skin was closed using simple interrupted sutures. Postoperatively, the patient was administered enrofloxacin, meloxicam, and topical gentamicin. Complete wound closure occurred by postoperative day 7, without complications.